Gastric antral vascular ectasia (Watermelon stomach); an unusual cause of upper gastrointestinal bleeding in elderly: A case report. (October 2022) - Lageju, Nimesh; Uprety, Pratik; Neupane, Durga; Bastola, Satish; Lama, Suhel; Panthi, Sagar; Gnawali, Arun
Abstract: Introduction: Gastric antral vascular ectasia (GAVE) is an unusual cause of upper gastrointestinal (GI) bleeding in an elderly patient. Case presentation: A 73-year-old female with erosive gastritis, hypertension, and unstable angina arrived at the emergency department with shortness of breath, easy fatigability, and melaena. Physical examination indicated pallor but no signs of distress, with an unremarkable systemic examination. Routine blood testing indicated anemia. The patient underwent upper gastrointestinal endoscopy, which revealed linear red ectatic vessels radiating from the antrum towards the body. A diagnosis of GAVE was made. Blood transfusions and argon plasma coagulation were undertaken. Clinical discussion: This condition is an uncommon cause of upper GI bleeding with the antrum being the most prevalent site. The pathophysiology of GAVE is yet unknown, however, many hypotheses have been postulated. GAVE is frequently misdiagnosed as gastritis. GAVE treatment comprises initial resuscitation and symptomatic treatment with intravenous fluids and blood products. Endoscopy has increasingly been the first-line therapeutic option for GAVE in recent years, including argon plasma coagulation. Conclusion: The diagnosis of gastric antral vascular ectasia is frequently overlooked during upper GI endoscopy, despite the fact that it should always be explored, especially in cases of unexplained GI bleeding in the elderly. Highlights: An unusual cause of upper gastrointestinal bleeding in an elderly patient. Frequently misdiagnosed as gastritis. Linear red ectatic vessels radiating from gastric antrum towards the body. Argon plasma coagulation is a good treatment modality.